Suomalaisen musiikkioppilaitosjärjestelmän tehtävä nyky-yhteiskunnassa : Ehdotelma systeemiseksi muutokseksi - Laes, Tuulikki; Westerlund, Heidi; Väkevä, Lauri; Juntunen, Marja-Leena (Suomen musiikkitieteellinen seura, 2018)
In this theoretical article, we examine the Finnish music school system as a social system whose unique role defines its boundaries and separates it from other systems (Luhmann 1995), and which must also renew its role in order to respond to societal changes. In our article, we focus particularly on the themes of equality of opportunities and equity. We argue that simply adhering to the theory of equality of opportunities, which forms the basis for contemporary educational systems, is not enough for the realization of equity in the music school system. Rather, the creation of a genuine equality of opportunities demands structural responsibility and active interventions from the system. If the music school system acknowledges that it increases inequality through maintaining an unbalanced division of cultural capital (Bourdieu 1986), it can redefine its role in current society so that the goal of equity in the public service system is the main criteria of quality. To support our claim, we will first examine the historical construction of the music school system’s binary (general and professional) role, which stems from different interpretations of the concept of Bildung. We will then examine, from Bourdieu’s sociological perspective, how the cultural capital produced by the music school system accumulates for the advantaged populations. We will demonstrate that, from the perspective of the equality of opportunities, the music school system seems to be failing in both of its fundamental tasks. Third, we will argue through two examples that the development of a more equitable music school demands a change of perspective, wherein the music school system redefines its role and truly commits to actions that will then fulfill its societal responsibility. Regarded from the systemic perspective, it is possible to carry out this change through social innovations, which will in turn increase institutional resilience. The role of the system has to be reshaped in order to expand its moral responsibility beyond its traditional musical and pedagogical aspects, to include broader societal concerns. This, in turn, calls for expanded professionalism among the professionals working within the music school system.
Keywords: tasa-arvo; koulutuspolitiikka; musiikkikasvatus